Analisis Pengaruh Kepercayaan dan Kualitas Produk terhadap Loyalitas Nasabah dengan Kepuasan Nasabah sebagai Media Intervening - Salilo, Febriana Amanda (JURNAL RISET BISNIS DAN MANAJEMEN, 2019)
The results of the research show that there are significant effects of trust towards commercial credit customer satisfaction in Panin Bank, Ltd. Manado Main Branch. The product quality has significant effect towards commercial credit customer in Panin Bank, Ltd. Manado Main Branch, whereas product quality does not affect significantly towards commercial credit customer loyalty in Panin Bank, Ltd. Manado Main Branch. Customer satisfaction has significant effects towards commercial credit customer loyalty in Panin Bank, Ltd. Manado Main Branch. Customer trust and Product quality have positive influences towards the loyalty of customers of commercial credit Bank Panin, Ltd. Manado Main branch through customer satisfactionKeywords: Marketing Management, Trust, Product Quality, Customer Satisfaction, Customer Loyalty